A descriptive analysis of crowdfunding in Mexico - Campos Avendaño, Daniela; Bernal Domínguez, Deyanira (Unidad Editorial UPTC, 2020)
Crowdfunding has become a valid alternative to finance social, cultural and business projects in the world. The present investigation is a descriptive analysis of the crowdfunding industry, financing through a crowd using the Internet, in Mexico. Its objective is to know the trend, the characteristics and the dynamics of the Mexican crowdfunding platforms. For this, an analysis of the data published in the web portals of the platforms was carried out. In turn, the growth of the sector is shown in terms of the number of platforms, initiatives launched, investors / funders participating and companies financed. The research shows that the industry has had an average growth of 48% in terms of platforms and that the innovations in the models of the platforms have taken place, mainly in those of a financial nature. Keywords: crowdfunding, platforms, rewards, debt, equity, donation. JEL Classification: G11, G23, G29. Recibidio: 15/03/2019.  Aceptado: 10/02/2020.  Publicado: 30/06/2020.